Simultaneous removal of organic matter and nitrogen compounds by combining a membrane bioreactor and a membrane biofilm reactor - Hasar, Halil (Elsevier Sci Ltd, 2009)
Hydrogen-based membrane biofilm reactors (MBfR) have been applied to the denitrification of nitrate-containing water and wastewater. Adding ail aerobic membrane bioreactor (MBR) to a MBfR provides significant nitrification and organic oxidation because most wastewater also contains a significant concentration of organic material and ammonium nitrogen. This study describes experiments that investigate the removal of organic and nitrogenous compounds in the combined MBR/MBfR system. The experiments demonstrate that the MBR/MBfR combination successfully performs COD oxidation and nitrogen removal for organic and ammonium loads in the ranges of 1000-4300 g COD/m(3)-d and 200-230 g N/m(3)-d, respectively. Total-nitrogen removal was controlled by nitrification in the MBR, because the MBfR denitrified all of the NO(3) provided by the MBR. The nitrate flux in the MBfR was in the range of 4-8 g N/m(2)-d for cases of almost complete denitrification (>99%): the H(2) flux was varied from 1.4 to 2.8 g H(2)/m(2)-d. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbon removal; Membrane bioreactor; Membrane-attached biofilm; Nitrification; Autohydrogenotrophic denitrification